Responsible Procreation—Co-Responsibility of Spouses. From Adequate Anthropology to the Legal Anthropology of Matrimony - Pastwa, Andrzej (Philosophy and Canon Law, 2020)
This study successfully verifies the thesis that both eponymous anthropological criteria (responsible procreation and co-responsibility of spouses), referring to the nature of personae humanae, have an invaluable epistemological value in the matrimonial law. Opening a wider horizon of cognition and interpretation, they become indispensable in the accurate/reliable deciding of cases concerning the invalidity of marriage. The subsequent stages of the discourse proposed here, step by step from the general guidelines of adequate anthropology to the detailed assumptions of the legal anthropology of matrimony, have very clearly confirmed the words of John Paul II that “[…] an authentically juridical consideration of marriage requires a metaphysical vision of the human person and of the conjugal relationship” (Address to the Roman Rota, 2004).